The Use of H5P Lumi Education Interactive Multimedia in Improving Students’ Cognitive Abilities in the Subject of Islamic Cultural History - Halimatus Sa'diah; Muhammad Ikbal; Suryadi Nasution; Anni Marhamah (Prodi Pendidikan Keagamaan Islam, 2025)
This study aimed to determine the improvement of students’ cognitive abilities using HSP lumi education interactive multimedia in the subject of Islamic cultural history. This study was conducted at MTsS Mardiyah Islamiyah Panyabungan using the classroom action research (CAR) method consisting of two cycles, each carried out in two meetings. The subjects of this study were 29 students of class VIII at-Tin. Data collection techniques used observation sheets, multiple choice tests, and interviews. The results of the study showed that the cognitive abilities of students increased. In the pre-action, the number of students who completed was only 7 people, who had not completed 22 people, with an average value of 59.55, and a classical completion rate of 24%, increasing in cycle I to 12 students who had completed, 17 students who had not completed, with an average value of 72.58, and a classical completion rate of 41%. And in cycle II, the number of students who completed increased again to 26 people, who had not completed only 3 people, with an average value of 84.44, and classical completion percentage of 89%. Based on these results, it can be concluded that the use of H5P lumi education interactive multimedia can improve students’ cognitive abilities in the subject of Islamic cultural history at MTsS Mardiyah Islamiyan with an increase of 65%.